2023 On-site Padua Days on Muscle and Mobiliy Medicine: Call for speakers - Sandra Zampieri; Carla Stecco; Marco Narici; Stefano Masiero; Ugo Carraro (PAGEPress Publications, 2022)
The winter of 2022 approaches with the need to finalize our plans for next year. This is urgent for the 2023 Meeting of the Padua Days of Muscle and Mobility Medicine (Pdm3) to be held March 29th to April 1st, 2023 at the Hotel Petrarca in the Thermae of Euganean Hills (Padua), Italy. A preliminary Pdm3 Program is almost ready with sessions, organzers and keynote speakers, but ther is still rooms for many interesting and interested young speakers. Some of the Pdm3 sessions dedicated to molecular and cellular myology are organized by old Pdm3 Friends, but there will also be interesting new entries, including those for Rehabilitation Sessions. No doubt that 2023 Pdm3 will attract old friends, but topics of a few sessions are at the frontiers of Translational Myology and new entries are most warmly acknowledged. This is true for both basic myology research, which include beside traditional MiRNA the new entry of the LNC-RNA and the "dark side of the genome". As to rehabilitation topics, beside the old friends of the "LBI workshop on muscle rehabilitation - from mouse to elderly", new entries are sessions on Muscle Fascia, Muscle Rehabilitation in Dentistry (that will organize also a Practical Course) and the session on "European Medical Thermalism and FEMTEC" that will also offer a practical Course. We hope that by January 20th, 2023 many old and new friends will send their abstracts to fill an half-empty program and then by May 1st, 2023 they submit Communications to EJTM that deserve them to increase the 2023 EJTM Impact Factor.